Noodleheads see the future - Arnold, Tedd; Hamilton, Martha; Weiss, Mitch, 1951- (Holiday House, 2018)
Inspired by folktales about fools from around the world, brothers Mac and Mac Noodlehead exasperate Uncle Ziti, are fooled by their friend Meatball, and make a garden for their mother.